Perfectionism and motivation for learning mathematics in higher education - Rovan, Daria (2013)
Present research sets out to complement and extend previous research on perfectionism in the context of learning mathematics in higher education exploring the different motivational profiles of students showing different levels of adaptive and maladaptive perfectionism. Constructs from two different motivational theories – achievement goals theory and self-efficacy theory – were used to indicate students' motivation, and students' approaches to learning were also examined. A sample of 362 undergraduate technical sciences students from University of Zagreb, Croatia participated in the study. All students were enrolled in introductory-level mathematics course. Students completed questionnaire on perfectionism measuring adaptive and maladaptive perfectionism, self-efficacy in mathematics, achievement goals in mathematics and approaches to learning. Results of cluster analysis revealed that three different types of perfectionism can be differentiated (non- perfectionists with low standards and low discrepancy, adaptive perfectionists with high standards and low discrepancy, maladaptive perfectionists with high standards and high discrepancy). Adaptive perfectionists are more likely to pursue mastery-approach than non- perfectionists and to pursue performance approach goals more likely than both maladaptive perfectionists and non-perfectionists. Maladaptive perfectionists are more likely to pursue mastery- avoidance and performance-avoidance goals than the other two groups, while non-perfectionists are the most prone to work avoidance goals. Adaptive perfectionists have the highest mathematics self- efficacy and use the most adaptive approaches to learning (high deep and strategic approach and low surface approach). These results support previous findings that setting high standards is beneficial to motivation and achievement, while it has detrimental effect only when accompanied by the perception of discrepancy between those standards and actual accomplishments.